FAKTOR – FAKTOR YANG MENENTUKAN SEWA TEMPAT TINGGAL PADA KAWASAN EKONOMI DAN PENDIDIKAN DI KOTA PALEMBANG - Chitra Puspitasari DN (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
The purpose of this paper is to analyze the influence Accessibility,Power Electric,Water Supply, Roominess, The Floor Level of Residential Rental in Economic Region and Education Region and the was difference between residential rental in economic and education region. Data used in this study are primary data obtained from interviews with respondents who guided the list of questions. analyze by using Ordinary Least Square (OLS). The result showed that variable of Power Electric, Water Supply and Roominess have significant effect to Residential Rental and then Accessibility and The Floor Level have not significant effect to Residential Rental in Economic Region and Education Region. Variable of Power Electric and The Floor Level have negative effect to Residential Rental. There is differences residential rental in Economic and Education Region. Residential rental in Education Region is greater than Economic Region.